2022
DOI: 10.3389/fpsyt.2022.874905
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Social Support and Loneliness, Self-Esteem, and Resilience Among Left-Behind Children in Mainland China: A Meta-Analysis

Abstract: BackgroundSocial support is frequently reported to be correlated with loneliness, self-esteem, and resilience among left-behind children in mainland China. However, to date, there is no consensus on the extent to which those factors are correlated with social support among left-behind children. We thus performed a meta-analysis to quantitatively synthesize the previous findings.MethodsTwo investigators systematically and independently searched PubMed, EMBASE, Web of Science, PsycINFO, Wan Fang, Chinese Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In this study, the moderating effect analysis of the study design found that sample size significantly affected the correlation between social support and nurse TI. Specifically, the correlation reported in studies with a sample size ≤1,000 was higher than that reported in studies with a sample size >1,000, which is consistent with the results of a previous meta-analysis ( 111 ). Existing evidence shows that there is a considerable correlation between the effect size and the sample size, that is, studies with a small sample size usually produce a larger effect size than those with a large sample size ( 112 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the moderating effect analysis of the study design found that sample size significantly affected the correlation between social support and nurse TI. Specifically, the correlation reported in studies with a sample size ≤1,000 was higher than that reported in studies with a sample size >1,000, which is consistent with the results of a previous meta-analysis ( 111 ). Existing evidence shows that there is a considerable correlation between the effect size and the sample size, that is, studies with a small sample size usually produce a larger effect size than those with a large sample size ( 112 ).…”
Section: Discussionsupporting
confidence: 90%
“…Jiang et al, 2019; Zhang et al, 2019) and in research published in English about left-behind children (e.g. Ao and Briffett Aktaş, 2022; Huang et al, 2022). However, some researchers who began their studies with these negative suppositions, actually found netural or even positive outcomes in their conclusions.…”
Section: Left-behind Young Children In China and Research About Themmentioning
confidence: 99%
“…An important limitation is the cross-sectional design which hinders a causal interpretation of the statistical associations. We believe that lack of close social relationships with parents and friends are the precursor of loneliness because prospective studies have shown that poor social relationships predict loneliness(Huang et al 2022). We acknowledge the possibility of a bi-directional relationship or a reverse causation, i.e.…”
mentioning
confidence: 92%
“…The Cohen effect sizes ranged from small to medium (Cohen 1988). There has been less examination of the associations between loneliness and adolescents' social relationships with parents, although there is evidence that emotional neglect in childhood predicts loneliness in adolescence (Musetti et al 2021); ndings from a meta-analysis showed a moderate correlation between loneliness and social support among children living apart from their parents (Huang et al 2022). Given that limited knowledge, there is a need to examine how loneliness is connected to different social relationships.…”
Section: Introductionmentioning
confidence: 99%